Six years of nitrous oxide emissions from temperate cropping systems under real-farm rotational management - Josette Garnier; Antoine Casquin; Benjamin Mercier; Anun Martinez; Eric Gréhan; Abdel Azougui; Sébastien Bosc; Alexandre Pomet; Gilles Billen; Bruno Mary (Agricultural and Forest Meteorology, 2024)

The role of potassium on maize leaf carbon exportation under drought condition - Elsa Martineau; Jean-Christophe Domec; Alexandre Bosc; Masako Dannoura; Yves Gibon; Camille Bénard; Lionel Jordan-Meille (Acta Physiologiae Plantarum, 2017)

Present and past genetic connectivity of the Indo‐Pacific tropical eel Anguilla bicolor - Yuki Minegishi; Pierre‐Alexandre Gagnaire; Jun Aoyama; Pierre Bosc; Eric Feunteun; Katsumi Tsukamoto; Patrick Berrebi (Journal of Biogeography, 2012)
Aim The objective of this study was to reveal the present population structure and infer the gene‐flow history of the Indo‐Pacific tropical eel Anguilla bicolor . Location The Indo‐Pacific region. Methods The entire mitochondrial control region sequence and the genotypes at six microsatellite loci were analysed for 234 specimens collected from eight representative localities where two subspecies have been historically designated. In order to infer the population structure, genetic differentiation estimates, analysis of molecular variance and gene‐tree reconstruction were performed. The history of migration events and population growth was assessed using neutrality tests based on allelic frequency spectrum, coalescent‐based estimation of gene flow and Bayesian demographic analysis using control region sequences. Results Population structure analysis showed genetic divergence between eels from the Indian and Pacific oceans ( F ST = 0.0174–0.0251, P 0.05 for microsatellites; Φ ST = 0.706, P 0.001 for control region), while no significant variation was observed within each ocean. Two mitochondrial sublineages that do not coincide with geographical regions were found in the Indian Ocean clade of a gene tree. However, these two sublineages were not differentiated at the microsatellite markers. The estimation of mitochondrial gene‐flow history suggested allopatric isolation between the Indian and Pacific oceans, and a possible secondary contact within the Indian Ocean after an initial population splitting. Bayesian demographic history reconstruction and neutrality tests indicated population growth in each ocean after the Indo‐Pacific divergence. Main conclusions Anguilla bicolor has diverged between the Indian and Pacific oceans, which is consistent with the classical subspecies designation, but is apparently genetically homogeneous in the Indian Ocean. The analysis of gene‐flow and demographic history indicated that the two mitochondrial sublineages observed in the Indian Ocean probably represent the haplotype groups of relict ancestral populations. A comparison with a sympatric congener suggested that absolute physical barriers to gene flow may not be necessary for population divergence in eels.

Strong seasonal disequilibrium measured between the oxygen isotope signals of leaf and soil CO 2 exchange - LISA WINGATE; JÉRÔME OGÉE; RÉGIS BURLETT; ALEXANDRE BOSC (Global Change Biology, 2010)
The oxygen isotope composition ( δ 18 O) of atmospheric CO 2 is among a very limited number of tools available to constrain estimates of the biospheric gross CO 2 fluxes, photosynthesis and respiration at large scales. However, the accuracy of the partitioning strongly depends on the extent of isotopic disequilibrium between the signals carried by these two gross fluxes. Chamber‐based field measurements of total CO 2 and CO 18 O fluxes from foliage and soil can help evaluate and refine our models of isotopic fractionation by plants and soils and validate the extent and pattern of isotopic disequilibrium within terrestrial ecosystems. Owing to sampling limitations in the past, such measurements have been very rare and covered only a few days. In this study, we coupled automated branch and soil chambers with tuneable diode laser absorption spectroscopy techniques to continuously capture the δ 18 O signals of foliage and soil CO 2 exchange in a Pinus pinaster Aït forest in France. Over the growing season, we observed a seasonally persistent isotopic disequilibrium between the δ 18 O signatures of net CO 2 fluxes from leaves and soils, except during rain events when the isotopic imbalance became temporarily weaker. Variations in the δ 18 O of CO 2 exchanged between leaves, soil and the atmosphere were well explained by theory describing changes in the oxygen isotope composition of ecosystem water pools in response to changes in leaf transpiration and soil evaporation.

Impact of severe dry season on net ecosystem exchange in the Neotropical rainforest of French Guiana - DAMIEN BONAL; ALEXANDRE BOSC; STÉPHANE PONTON; JEAN‐YVES GORET; BENOÎT BURBAN; PATRICK GROSS; JEAN‐MARC BONNEFOND; JAN ELBERS; BERNARD LONGDOZ; DANIEL EPRON; JEAN‐MARC GUEHL; ANDRÉ GRANIER (Global Change Biology, 2008)
The lack of information on the ways seasonal drought modifies the CO 2 exchange between Neotropical rainforest ecosystems and the atmosphere and the resulting carbon balance hinders our ability to precisely predict how these ecosystems will respond as global environmental changes force them to face increasingly contrasting conditions in the future. To address this issue, seasonal variations in daily net ecosystem productivity (NEP d ) and two main components of this productivity, daily total ecosystem respiration ( R Ed ) and daily gross ecosystem productivity (GEP d ), were estimated over 2 years at a flux tower site in French Guiana, South America (5 °16′54″N, 52 °54′44″W). We compared seasonal variations between wet and dry periods and between dry periods of contrasting levels of intensity (i.e. mild vs. severe) during equivalent 93‐day periods. During the wet periods, the ecosystem was almost in balance with the atmosphere (storage of 9.0 g C m −2 ). Seasonal dry periods, regardless of their severity, are associated with higher incident radiation and lower R Ed combined with reduced soil respiration associated with low soil water availability. During the mild dry period, as is normally the case in this region, the amount of carbon stored in the ecosystem was 32.7 g C m −2 . Severe drought conditions resulted in even lower R Ed , whereas the photosynthetic activity was only moderately reduced and no change in canopy structure was observed. Thus, the severe dry period was characterized by greater carbon storage (64.6 g C m −2 ), emphasizing that environmental conditions, such as during a severe drought, modify the CO 2 exchange between Neotropical rainforest ecosystems and the atmosphere and potentially the resulting carbon balance.